Genetic and Symbiotic Diversity of Nitrogen-Fixing Bacteria Isolated from Agricultural Soils in the Western Amazon by Using Cowpea as the Trap Plant - Azarias Guimarães, Amanda (American Society for Microbiology, 2012)
Cowpea is a legume of great agronomic importance that establishes symbiotic relationships with nitrogen-fixing bacteria. However, little is known about the genetic and symbiotic diversity of these bacteria in distinct ecosystems. Our study evaluated the genetic diversity and symbiotic efficiencies of 119 bacterial strains isolated from agriculture soils in the western Amazon using cowpea as a trap plant. These strains were clustered into 11 cultural groups according to growth rate and pH. The 57 nonnodulating strains were predominantly fast growing and acidifying, indicating a high incidence of endophytic strains in the nodules. The other 62 strains, authenticated as nodulating bacteria, exhibited various symbiotic efficiencies, with 68% of strains promoting a significant increase in shoot dry matter of cowpea compared with the control with no inoculation and low levels of mineral nitrogen. Fifty genotypes with 70% similarity and 21 genotypes with 30% similarity were obtained through repetitive DNA sequence (BOX element)-based PCR (BOX-PCR) clustering. The 16S rRNA gene sequencing of strains representative of BOX-PCR clusters showed a predominance of bacteria from the genus Bradyrhizobium but with high species diversity. Rhizobium, Burkholderia, and Achromobacter species were also identified. These results support observations of cowpea promiscuity and demonstrate the high symbiotic and genetic diversity of rhizobia species in areas under cultivation in the western Amazon.